Pediatric Idiopathic Intracranial Hypertension - Gaier, Eric D.; Heidary, Gena (Seminars in Neurology, 2019)
The presentation of idiopathic intracranial hypertension (IIH) in pediatric populations has several important distinctions from that in adults, especially among prepubertal patients, in which there is no apparent association with gender or obesity. Pediatric patients are more likely to be asymptomatic or present with atypical symptoms than their adult counterparts, posing a diagnostic challenge in some cases. It is important to be aware of the ways in which diagnostic criteria for IIH are modified from that of adults. Ideal treatment practices and the natural history of pediatric IIH remain unclear. Acetazolamide is the mainstay of medical treatment, but some patients with significant visual loss may require surgical intervention. Multicenter studies to accrue a large number of cases and future prospective studies will help to better define pediatric IIH and to formulate consensus guidelines for treatment and management of these patients.
Keywords: idiopathic intracranial hypertension; pseudotumor cerebri; papilledema